Labor Markets for Inclusive Growth - World Bank (Washington, DC, 2014)
This policy note outlines short, and medium-term policy options for addressing critical challenges affecting labor markets in Mexico, and in particular labor productivity. As labor is the main source of income for most of the population, poverty is closely linked to underemployment and low wages. Yet labor markets have played a limited role in poverty reduction in Mexico. Labor income accounted for just 22 percent of the decline in poverty in Mexico over the last decade compared with 38 percent in the rest of the region. Between the third quarter of 2008 and the third quarter of 2011, the labor income poverty index2 continued to decline in Brazil, Ecuador, and Peru but increased in Mexico. The equivalent measure produced by CONEVAL (Consejo Nacional de Evaluation), shows the labor poverty trend to be increasing through the first quarter of 2012. Finding the right bundle of policies to improve labor productivity and the functioning of the labor markets can serve to improve economic growth and welfare outcomes.